2022
DOI: 10.3390/ma15072416
|View full text |Cite
|
Sign up to set email alerts
|

Development of Y2O3 Dispersion-Strengthened Copper Alloy by Sol-Gel Method

Abstract: In this study, oxide dispersion-strengthened Cu alloy with a Y2O3 content of 1 wt.% was fabricated through citric acid sol-gel synthesis and spark plasma sintering (SPS). The citric acid sol-gel method provides molecular mixing for the preparation of precursor powders, which produces nanoscale and uniformly distributed Y2O3 particles in an ultrafine-grained Cu matrix. The effects of nanoscale Y2O3 particles on the microstructure, mechanical properties and thermal conductivity of the Cu-1wt.%Y2O3 alloy were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…(2) Rare earth elements adsorb other alloying elements and increase the concentration gradient of alloying elements, resulting in local component undercooling and enhanced heterogeneous nucleation of liquid metal matrix. (3) The composition undercooling caused by element segregation results in the formation of segregated compounds and the formation of hetero nucleation sites [ 3 , 45 , 46 , 47 ].…”
Section: Interface Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Rare earth elements adsorb other alloying elements and increase the concentration gradient of alloying elements, resulting in local component undercooling and enhanced heterogeneous nucleation of liquid metal matrix. (3) The composition undercooling caused by element segregation results in the formation of segregated compounds and the formation of hetero nucleation sites [ 3 , 45 , 46 , 47 ].…”
Section: Interface Characteristicsmentioning
confidence: 99%
“…Internal reinforcing particles in the grain boundary and grain have also been found to enhance concrete strength, refining the grain by a pinning effect. Ke et al prepared copper alloy with Y 2 O 3 content of 1% by spark plasma sintering (SPS) [ 47 ]. The results showed that Y 2 O 3 particles were evenly distributed in the grain, while dispersing nanoparticles in the grain was an effective method to improve strength and ductility.…”
Section: Interface Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ke et al [ 21 ] contributed a paper entitled “Development of Y 2 O 3 Dispersion-Strengthened Copper Alloy by Sol-Gel Method”, which demonstrates an oxide dispersion-strengthened Cu alloy with a content of 1 wt.% nanoscale and uniformly distributed Y 2 O 3 particles in an ultra-fine-grained Cu matrix fabricated through citric acid sol–gel synthesis and spark plasma sintering (SPS). The unique microstructure provides excellent mechanical properties with a tensile strength of 572 MPa and a total elongation of 6.4%, together with high thermal conductivity.…”
mentioning
confidence: 99%